ANALISIS KECERDASAN EMOSIONAL DENGAN STRATEGI KOPING PADA REMAJA AKHIR DI SMA NEGERI 3 SAMARINDA - Wahab, Lutfi Nur Amalia; Burhanto; Hidayat, Faried Rahman (Caring : Jurnal Keperawatan, 2025)
ABSTRACT In the process of human life where there will be changes such as physical, social, emotional, and psychosocial from the transition period of childhood to adulthood. Emotionally intelligent people are able to control their emotions well from excessive stress, depression, anxiety, or anger and restrain or delay their temporary pleasure in pursuit of long-term goals. The purpose of this study was to determine the relationship between emotional intelligence and coping strategies in late adolescents at SMA Negeri 3 Samarinda. This research is quantitative correlation with a Cross Sectional approach, with a sample of 178 using stratified random sampling technique. The instruments used were the TEIQue emotional intelligence questionnaire and the Brief Cope coping strategy. Data analysis used the Spearman Rank test. The results of statistical tests between emotional intelligence and coping strategies in late adolescents obtained a correlation coefficient of -0.157 and the p value is 0.037 less than the significance level of 0.05. This is a significant relationship between emotional intelligence and coping strategies in late adolescents at SMA Negeri 3 Samarinda and shows a weak relationship with a negative correlation direction that the lower the emotional intelligence they have, the more adaptive their coping strategies are.